Earthquake and Elderly: A Psychosocial Perspective - Ali Emre ŞEVİK (Yaşlı Sorunları Araştırma Derneği, 2023)
Earthquakes are natural disasters that cause the most deaths, serious injuries and loss of limbs worldwide today. As one of the most important natural events with inevitable, untimely and de-structive effects, which cause high economic losses and costs for societies, it has deeply affected humanity and many societies in different geographies throughout the history of civilization and continues to affect it. Our country, where the traces of the historical effects of the earthquakes in the past can still be seen, had to face a new earthquake phenomenon in the near future. Our society, which continues to experience traumas due to the earthquake, has to learn to live with the earth-quake in the future. While the earthquake negatively affects almost all of the society, especially the individuals in the earthquake area, it affects especially vulnerable individuals, especially the disa-bled, children and the elderly, more severely and negatively, with the socio-economic problems and mental health problems it causes. These vulnerable groups of the society are affected by natu-ral disasters at different levels depending on variables such as social class, occupation, ethnicity, gender, disability, health status, age and immigration status, as well as the general society. As an inevitable result of the changing demographic structure of societies on a global scale, older adults, who constitute an increasing part of the population, are among the most vulnerable groups against the sudden and unexpected effects of natural disasters. In our country where the elderly popula-tion is increasing rapidly, it is a current necessity to deal with the mental health problems of the elderly population due to earthquakes in a privileged way. From this point of view, in our study, the effects of the earthquake as a natural event on human life will be briefly discussed, the general characteristics of old age will be mentioned, then by focusing on the psychosocial problems that the earthquake may cause on the elderly, one of the vulnerable social groups, and suggestions will be made for the elderly not to experience these problems.